กลยุทธ์การสื่อสารในภาวะวิกฤตและการฟื้นฟูภาพลักษณ์ของสถานีโทรทัศน์เนชั่นทีวี - พิมพ์ชญา ภมรพล (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
The objective of this research study are (1) to study communication strategies of crisis managementof Nation TV and (2) to study communication strategies of image restoration of Nation TV. Mixed method including content analysis of Nation TV s content in crisis communications and image restoration and in-depth interviews with Nation TV seniors management about inform policy decision and stratrgies communication planning. By choosing Nation TV crisis case that occurred during August-December 2020. The findings from the study found that Nation TV has the main strategy: reminding the organization s position, showing a victimage and denying allegations. After that Nation TV has changed communication approach that focuses on correcting mistakes instead of negative responding to crises. In terms of rebranding, it was found correcting undesirable image by returning to the principles of good journalism and focus on new target audience. The recommendations from this study present the context of crisis management with intense media governance by civil society and rebranding Nation TV in sustainable way.